Islamic Republic of Mauritania : Third Review Under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for the Islamic Republic of Mauritania. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper discusses Islamic Republic of Mauritania's Third Review of Arrangement under the Extended Credit Facility. The program aims at entrenching macroeconomic stability, supporting inclusive and job creating growth, and building international reserve buffers. The authorities plan to use the prospective fiscal space prudently for priority social spending-education, health, and social protection-and public infrastructure. The economic outlook has improved, buoyed by more favorable terms of trade and the upcoming development of a large offshore gas field. Growth is projected to accelerate to 6 3/4 percent this year, supported by a recovery in extractive sectors and continued broad-based non-extractive growth reflecting strong domestic demand and budding diversification. Downside risks related to global economic developments, commodity price volatility, and regional security concerns remain elevated. Considerable challenges remain to entrench macroeconomic stability, support inclusive growth, and build resilience to shocks. The prospective fiscal space should be used prudently for priority social policies and public infrastructure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet